Factors That Affect Financial Stability Of Listed Firms – Case Of Croatia - Tomislava Pavić Kramarić; Marko Miletić (Elektronički Zbornik Radova Veleučilišta u Šibeniku)
This paper explores the factors affecting the financial stability of publicly traded companies. The sample includes non-financial companies listed on the prime and official markets of the Zagreb Stock Exchange from 2018 to 2022. In order to conduct the analysis, a variety of firm-specific, industry-specific and macroeconomic factors were utilized, encompassing company size measured with sales, liquidity expressed with the quick ratio, leverage, earnings per share, Covid-19 dummy variable and inflation. Additionally, financial stability was measured using a variant of the Z-score indicator. The results of the analysis conducted using Arellano-Bond dynamic panel model reveal that variables that are statistically significant in explaining financial stability are size, liquidity, and earnings per share with all three having positive influence on the financial stability of Croatian listed non-financial companies.